Conceptual design of a palm oil hydrotreatment reactor for commercial diesel production (2014)
A reactor with an industrial production of renewable diesel via palm oil hydrotreatment was conceptually designed based on laboratory-scale continuous and semi-batch reactor experiments. The conversion of vegetable oil to biodiesel through transesterication is responsible for a reduction in the use of a signi cant fraction of fossil fuels. Unfortunately, the diesel produced by transesterication has limitations such as high density, high viscosity and low cetane number. An alternative to transesteri cation is the hydrotreatment (HDT) of vegetable oils to produce a fuel with properties more similar to petroleum diésel than those of diesel obtained by transesterication. This thesis presents hydrotreating as an alternative for the production of renewable diesel in Colombia. It proposes a reaction pathway for hydrotreatment based on experiments with Rened, Bleached and Deodorized Palm Oil (RBDPO) and using a comercial solid trilobite NiMo catalyst (NiMo/).